A method for selecting modified DNAzymes without the use of modified DNA as a template in PCR. Issue 7 (9th December 2014) - Renders, Marleen; Miller, Emily; Hollenstein, Marcel; Perrin, David
Abstract : Linking phenotype to genotype for modified DNAzyme selections: we report a method for selecting modified DNA catalysts without having to amplify modified DNA as the unmodified DNA coding strand (genotype) is liberated as a function of catalysis by the modified phenotypic strand. Abstract : Modified DNAzyme selections typically depend on recopying catalytically active modified DNA (mDNA) into cDNA in a PCR amplification step. However mDNA is often a poor template in PCR. Herein we propose a selection method in which the catalytically active, mDNA strand is covalently linked to the unmodified DNA template strand from which it was polymerized. Following selection, the unmodified DNA template is amplified in a PCR instead of the mDNA. This method circumvents the PCR amplification of mDNA.